2008
DOI: 10.1242/jeb.017590
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of slow turn maneuvering in the fruit batCynopterus brachyotis

Abstract: SUMMARYManeuvering abilities have long been considered key factors that influence habitat selection and foraging strategies in bats. To date, however, very little experimental work has been carried out to understand the mechanisms that bats use to perform maneuvers. In the present study, we examined the kinematics of slow-speed turning flight in the lesser short-nosed fruit bat, Cynopterus brachyotis, to understand the basic mechanics employed to perform maneuvers and to compare them with previous findings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 36 publications
5
69
0
Order By: Relevance
“…Detailed analysis of the wing motion and body orientation during 90-degree turns in the pteropodid Cynopterus brachyotis showed that during the upstroke the body rotates into the direction of the turn, a mix of roll and yaw rotations, without changes in flight direction. This body rotation allows the bat to use part of the thrust generated during the downstroke to enhance the centripetal force from the bank turn, thus allowing the bat to perform tighter turns than predicted by wing morphology alone (Iriarte-Díaz and Swartz, 2008). These results highlights the importance of studying the mechanics flight performance and that using morphological proxies to estimate performance (e.g., wing loading and aspect ratio) might severely underestimate flight abilities of bats.…”
Section: Maneuvering During Flightmentioning
confidence: 89%
“…Detailed analysis of the wing motion and body orientation during 90-degree turns in the pteropodid Cynopterus brachyotis showed that during the upstroke the body rotates into the direction of the turn, a mix of roll and yaw rotations, without changes in flight direction. This body rotation allows the bat to use part of the thrust generated during the downstroke to enhance the centripetal force from the bank turn, thus allowing the bat to perform tighter turns than predicted by wing morphology alone (Iriarte-Díaz and Swartz, 2008). These results highlights the importance of studying the mechanics flight performance and that using morphological proxies to estimate performance (e.g., wing loading and aspect ratio) might severely underestimate flight abilities of bats.…”
Section: Maneuvering During Flightmentioning
confidence: 89%
“…The joint trajectory patterns have been extracted from the bio-inspired analysis of bat turning flight carried out in [12], [24] and [32].…”
Section: Maneuversmentioning
confidence: 99%
“…We will make this assumption for further simplicity. Then, again using the same approach as before, we obtain β w = arctan V sin α + rφ V cos α + rψ (27) and α w = β w + θ w (28) with r denoting the length to the center of pressure for a straight wing. This formulation retains the fact that we can have induced velocity from each of the motions, which is necessary for thrust generation by proper turning of the resultant force vector.…”
Section: Ab Local Velocity Calcualationmentioning
confidence: 99%